2009
DOI: 10.1021/jp809235x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Carbon Nanotube Electrode Arrays: Effect of Length of the Linker between Nanotubes and Electrode

Abstract: The influence of the length of the carbon chain of a self-assembled monolayer (SAM) on gold electrodes on the electrochemical performance of carbon nanotube arrays attached to the SAM was explored. Four electrode constructs were assessed, all of which were modified with four different lengths (C2−C11) of amine-terminated alkanethiols. The four constructs were gold electrodes modified (1) with SAMs alone, (2) with carbon nanotubes randomly dispersed onto the SAM-modified electrodes by drop coating, (3) with ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
79
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 78 publications
15
79
1
3
Order By: Relevance
“…This effect of the aliphatic chain thiol has been frequently observed at SAM modified electrodes (Chou et al, 2009;Su et al,2006). The sequential self-assembly of the AuNR 1 layer has determined a decrease of the charge transfer resistance by 3 orders of magnitude (n = 2, table 2).…”
Section: Electrochemical Characterization Of Multilayers Containing Smentioning
confidence: 73%
See 2 more Smart Citations
“…This effect of the aliphatic chain thiol has been frequently observed at SAM modified electrodes (Chou et al, 2009;Su et al,2006). The sequential self-assembly of the AuNR 1 layer has determined a decrease of the charge transfer resistance by 3 orders of magnitude (n = 2, table 2).…”
Section: Electrochemical Characterization Of Multilayers Containing Smentioning
confidence: 73%
“…The Faradaic process was highly hindered by the 1,6hexanedithiol layers ( Figure 5, n= 1, 3, 5, 7). This electrochemical behaviour is caused by the insulating properties of this dithiol when self-assembled on gold electrodes (Chirea et al, 2009(Chirea et al, , 2010Chou et al, 2009). For example, the first layer self-assembled on the gold electrodes determined a disappearance of the Faradaic currents in the cyclic and square wave voltammograms ( Figure 5, n = 1, black curve) as compared to the bare gold electrode ( Figure 5, n=0, dashed black curve) illustrating a dense packing of the 1,6hexanedithiol layer on the gold electrodes.…”
Section: Electrochemical Characterization Of 16hexanedithiol/gold Namentioning
confidence: 99%
See 1 more Smart Citation
“…Among these two approaches, most of the researchers preferred to choose the amide bond as the linking bridge to fix the shortened SWNTs on substrates. [44,[46][47][48]50,[65][66][67][71][72][73][94][95][96][97][98][99][100] This is possibly due to the high stability of amide bond and the high efficiency of the condensation reaction between carboxylic and amino groups. Figure 5B shows the typical tapping mode AFM image of v-SWNTs prepared on gold substrates using surface condensation reaction.…”
Section: Preparation Of Vertically Aligned Swnts Via Surface Condensamentioning
confidence: 99%
“…Diao and colleges Diao & Liu (2005) shown that the adsorbed SWCNTs act as many "electron relay stations" that mediate electrons between the metal electrode and redox centers. Also it is noted that the linking bonds at the ends of the tubes ensure an high electron transfer between nanotubes and surfaces Chidsey et al (1990);Cui, Primak, Zarate, Tomfohr, Sankey, Moore, Moore, Gust, Harris & Lindsay (2001);Cui et al (2002);Finklea & Hanshew (1992); Koehne et al (2004) but Gooding et al Chou et al (2009) reported that the electron-transfer rate at the nanotube-modified electrodes decayed exponentially with distance when the chain of the molecule bridge is increased. In this context our recent study on the combined effect on height and surface density of nanotubes give an overall point of view of HET dynamics in SWCNT forests Lamberti et al (2011).…”
Section: Redox Species Dissolved In Solutionmentioning
confidence: 99%